A scoping review of bryophyte microbiota: diverse microbial communities in small plant packages. (10th May 2022) - Chen, Ko-Hsuan; Nelson, Jessica
Abstract: Plant health depends not only on the condition of the plant itself but also on its diverse community of microbes, or microbiota. Just like the better-studied angiosperms, bryophytes (mosses, liverworts, and hornworts) harbor diverse communities of bacteria, archaea, fungi, and other microbial eukaryotes. Bryophytes are increasingly recognized as important model systems for understanding plant evolution, development, physiology, and symbiotic interactions. Much of the work on bryophyte microbiota in the past focused on specific symbiont types for each bryophyte group, but more recent studies are taking a broader view acknowledging the coexistence of diverse microbial communities in bryophytes. Therefore, this review integrates studies of bryophyte microbes from both perspectives to provide a holistic view of the existing research for each bryophyte group and on key themes. The systematic search also reveals the taxonomic and geographic biases in this field, including a severe under-representation of the tropics, very few studies on viruses or eukaryotic microbes beyond fungi, and a focus on mycorrhizal fungi studies in liverworts. Such gaps may have led to errors in conclusions about evolutionary patterns in symbiosis. This analysis points to a wealth of future research directions that promise to reveal how the distinct life cycles and physiology of bryophytes interact with their microbiota. Abstract : This review presents a holistic view of bryophyte–microbe interaction research over the past 40 years, tracing the field's development from focusing on individual symbionts to a broader microbiota view.